CONSTITUTIONAL TEXTS IN THE FIELD OF FUNDAMENTAL RIGHTS - Zainulabdeen Khalid Atiyah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Fundamental rights are the first nucleus that has pushed the constitutions of the world to strive for a kind of balance between power and freedom. This concept seeks to achieve a degree of peaceful coexistence between individuals who demand the need to respect their rights and freedom resulting from natural law and those in power. Accordingly, the present study is based on showing the specificity of the constitutional texts in the field of fundamental human rights and the extent to which these texts are affected by the considerations that take into account the will of the people and the constitutional judiciary, which prompted the proponents of the theory of the sovereignty of Parliament to ensure respect for the constitutional texts intended to be applied by the constitutional judge. The present study also indicates that the validity of the applicable fundamentalist rules to resolve the apparent conflict between the constitutional texts and other legal texts has not been proven due to the specificity of the constitutional texts in the field of fundamental rights.